Eksplorasi Alam Lewat Permainan: Strategi Pembelajaran Tematik Berbasis Outdoor Play - Ade Ismail Fahmi; Mia Audina Musyadad; Meilia Prehartanti; Rendi Atnanto; Marwah Triyati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Early childhood learning requires an approach that is appropriate to the characteristics of child development, including through play and nature exploration. Amidst the challenges of conventional learning, which tends to be dominated by classroom activities, the outdoor play approach is an innovative alternative that brings children closer to the real environment and contextual learning. This study aims to describe the implementation of thematic learning strategies based on outdoor play at RA Cahaya Iman, Telagasari District, and identify its contribution to the engagement and development of early childhood. This study uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The research subjects were class teachers and group B students. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions, with validity testing through triangulation of sources and techniques. The results of the study indicate that outdoor play is thematically integrated through exploratory activities based on the surrounding nature such as school gardens, parks, and open yards. These activities increase children's active involvement, facilitate social interaction, and foster curiosity and independence. The implications of this study indicate that nature-based learning can be an effective strategy in early childhood education, as well as a foundation for the development of a contextual and child-friendly curriculum.